2D Lead Dihalides for High‐Performance Ultraviolet Photodetectors and their Detection Mechanism Investigation. Issue 47 (6th November 2017) - Tan, Manlin; Hu, Chao; Lan, Yang; Khan, Jahangeer; Deng, Hui; Yang, Xiaokun; Wang, Peixiang; Yu, Xiangxiang; Lai, Jianjun; Song, Haisheng
Abstract: 2D halide semiconductors, a new family of 2D materials in addition to transition metal dichalcogenides, present ultralow dark current and high light conversion yield, which hold great potential in photoconductive detectors. Herein, a facile aqueous solution method is developed for the preparation of large‐scale 2D lead dihalide nanosheets (PbF2‐ x I x ). High‐performance UV photodetectors are successfully implemented based on 2D PbF2‐ x I x nanosheets. By modulating the components of halogens, the bandgap of PbF2‐ x I x nanosheets can be tuned to meet varied detection spectra. The photoresponse dependence on incident power density, wavelength, detection environment, and temperature are systematically studied to investigate their detection mechanism. For PbI2 photodetectors, they are dominantly driven by a photoconduction mechanism and show a fast response speed and a low noise current density. A high normalized detectivity of 1.5 × 10 12 Jones and an I ON / I OFF ratio up to 10 3 are reached. On the other hand, PbFI photodetectors demonstrate a photogating mechanism mediated by trap states showing high responsivity. The novel 2D halide materials with wide bandgaps, superior detection performance, and facile synthesis process can enrich the Van der Waals solids family and hold great potential for a wide variety of applications in advanced optoelectronics. Abstract : 2D lead dihalide semiconductors (PbX2, X = I, F), a new family of 2D materials in addition to transition metal dichalcogenides, are developed by an aqueous method. Their photoconductive detectors present ultralow dark current and high‐light‐conversion yield. Thus, such new 2D UV photodetectors demonstrate high responsivity and ultralow noise. Systematical study is also implemented to unravel their distinct detection mechanisms.